2021
DOI: 10.1186/s12913-021-06835-0
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization, psychological and emotional trauma among frontline health care workers treated for COVID-19 in Lagos State, Nigeria: a qualitative study

Abstract: Background COVID-19 pandemic has resulted in global health and economic crisis. We investigated the experiences of frontline health care workers recovering from COVID-19 in Lagos State Nigeria. Methods We conducted a qualitative study among frontline health workers recovering from COVID-19 in Lagos State, Nigeria. We interviewed 12 respondents before achieving data saturation. We used a checklist to guide the interview according to the phenomenon u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…This was consistent with study's findings in Nigeria that found that healthcare workers who had contracted COVID-19 experienced stigma and discrimination. 29 Findings by Mostafa 6 are that Egyptian healthcare workers experienced stigmatisation. Social ostracism including being evicted from rented accommodation faced by some participants was also observed in another study.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with study's findings in Nigeria that found that healthcare workers who had contracted COVID-19 experienced stigma and discrimination. 29 Findings by Mostafa 6 are that Egyptian healthcare workers experienced stigmatisation. Social ostracism including being evicted from rented accommodation faced by some participants was also observed in another study.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the study findings that indicates that people living with HIV had higher odds of having symptoms for COVID-19 and not getting tested; and lower odds of testing positive for COVID-19 infection. Concerns about stigma and discrimination for a positive COVID-19 result are salient [ 39 ] especially for people living with HIV who have had to deal with stigma and discrimination from being HIV positive [ 40 ]. These study results indicating that people living with HIV are at low risk for COVID-19 infection in the region should therefore, be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Penyajian informasi yang beragam, nampaknya menjadi konsumsi seharihari bagi masyarakat. Tak hanya mengakses informasi, masyarakat pun turut membagikan informasi yang banyak beredar di media sosial mengenai Covid-19 (Favero, Jilke, Wolfson, Xu, & Young, 2021;Kwaghe et al, 2021).…”
Section: Pendahuluanunclassified